Travelogue pour un Marco Polo [My Travels with Claude?]: A journey through the composer’s life and work in 10 days - Rogers, Stephen (Circuit, 2008)
AbstractIn his article, Stephen Rogers puts forward an interpretation of the work of Claude Vivier and its particular relationship(s) with travel. It is a reflective work which aims less at analysis than description. Those familiar with the techniques and gestures which Vivier used to create his music will recognize some of the same techniques applied in Rogers’ paper to the written rather than the sonic world.